THE EFFECT OF EDUCATIONAL BACKGROUND LEVEL AND AGE OF PARENTS TOWARDS STUDENTS' LEARNING OUTCOMES IN ONLINE LEARNING - Shinta Rosiana Dewi; Almuntaqo Zainuddin (Universitas PGRI Yogyakarta, 2022)
This research aims to determine the effect of parents’ educational background level and the age on the elementary school students’ learning outcomes in the implementation of online learning during the Covid-19 pandemic. The research was conducted at Kutowinangun 08 State Elementary School, Kutowinangun Lor, Tingkir, Salatiga City. The research was carried out in July for two weeks. The research sample was determined by using a cluster sampling consisting of all parents of fourth grade students. Multiple linear regressions test was employed to analyze the data. The findings showed that 1) There is an effect between the level of the parents’ educational background level on the students’ learning outcomes which shows the obtained of 2.441 > 2.052 and the significance value shows Sig. 0.022 < 0.05; 2) There is an effect between the age of parents on the students’ learning outcomes which shows the obtained of 2.181 > 2.052 and the significance value shows Sig. 0.038 < 0.05; 3) There is an effect between the parents’ educational background level and the parents’ age on the students’ learning outcomes which shows the obtained of 17.804 > 3.34 and the significance value shows Sig. 0.000 < 0.05.